Use of hormones. - Bell, T.D.; Smith, W.H.; Erhart, A.B.; Gardner, A.W.; Mackintosh, D.L.; Soule, R. (Kansas Agricultural Experiment Station, 2011)
In the lamb-feeding tests at the Garden City Branch Station during the 1953-54 feeding season, one lot of 48 lambs was given stilbestrol implants of varying sizes at the beginning of the feeding period. Another lot of 48 lambs was given stilbestrol-progesterone implants at two different dosage levels at the beginning of the feeding period. The performance of these lambs was compared with those in another group of 48 receiving a similar ration of ground sorghum fodder, sorghum grain, protein supplement, and limestone-but no hormone treatment. The preliminary results of the feedlot studies were presented in the 41st Annual Livestock Feeders' Day report of May 1, 1964. Additional feedlot, slaughter, and carcass data were obtained from these lambs and are presented in Table 4.
Keywords: Sheep; Hormones; Stilbestrol; Performance